Investigation of electron beam transport in a magnetron gun with a secondary-emission cathode - Dovbnya, A.N.; Zakutin, V.V.; Reshetnyak, N.G. (Вопросы атомной науки и техники, 2006)
Results are reported from the studies of electron beam generation in the magnetron gun and beam transport over
distances of 3 and 40 mm. The studies have demonstrated that the beam current and the beam dimensions remain
unchanged with the beam transport over a distance of 40 mm from the gun in the increasing magnetic field, the latter
being 10 to 15% higher at the Faraday cup than at the cathode. Приведены результаты исследования генерации и транспортировки электронных пучков магнетронной
пушки на расстояние 3 и 40 мм. Исследования показали, что ток пучка и его размеры не изменяются при
транспортировке пучка на расстояние 40 мм от пушки в нарастающем магнитном поле, которое на цилиндре
Фарадея больше поля на катоде на 10…15%. Приведені результати дослідження генерації та транспортування електронних пучків магнетронної
гармати на відстань 3 і 40 мм. Дослідження показали, що струм пучка та його розміри не змінюються при
транспортуванні пучка на відстань 40 мм від гармати в наростаючому магнітному полі, яке на циліндрі
Фарадея більше поля на катоді на 10…15%.